The Impact of Corporate Governance on Firm Value with Corporate Environmental Disclosure as Intervening Variable: Evidence from Indonesia - Puteri Kamila (Return : Study of Management, Economic and Bussines, 2025)
The worldwide quest for sustainability necessitates the active involvement of the corporate sector. The challenge for businesses has been to strategically integrate environmental disclosure into their broader corporate governance framework to enhance company value through effective governance and increased environmental transparency. This study investigates the influence of corporate governance on company value, utilizing corporate environmental disclosure as an intermediary variable. We utilize GRI's checklist to obtain an environmental disclosure index and assess firm value by Tobin's Q. This study used a variance-based partial least squares structural equation modeling (PLS-SEM) approach with WarpPLS 5.0 software for data analysis. The findings indicate that more corporate environmental transparency enhances business value. Corporate environmental disclosure was found to mediate the relationship between board size, the frequency of board meetings, and company value. The dimensions of the board and the frequency of board meetings positively correlate with corporate environmental disclosures and company value. In conclusion, the findings are beneficial for regulators, policymakers, and corporate managers to assess the influence of Corporate Governance and Environmental Disclosure regulations on enhancing market expectations and augmenting firm value. This has important implications for the current policy approach prevailing in Indonesia.